Training: Anti-Corruption Educational and Cultural Communication Strategy with a Pragmatic and Approach Communal Challenge - Agus Santoso, Aris Prio; Rozzaq Wijaya, Rahmaditya Khadifa Abdul (Abdi Masyarakat, 2024)
Currently, corruption has permeated various levels of administration, including at the village level such as Selomarto Village, Giriwoyo District, Wonogiri Regency. Both village officials and the general public are involved in daily corrupt practices, posing significant challenges to the integrity of village fund management. To address this issue, Training on Communication Strategies for Anti-Corruption Education and Culture was conducted with a Pragmatic and Communal Challenge Approach as part of Community Engagement in the Village. The results of this engagement indicate that the implemented communication strategy successfully increased awareness, participation, and commitment of Selomarto Village community members in combating corruption. The community effectively implemented strict oversight of village funds and conducted sustained social campaigns, building a strong anti-corruption culture. The commitment of the PKK Empowerment and Family Welfare Community in Selomarto Village as a change agent in corruption prevention serves as an inspiration to other regions, although ongoing challenges such as continuous support from various stakeholders remain a primary focus. Therefore, efforts to sustain local governance integrity and continuity should be continuously promoted to ensure the positive effects of this engagement continue to grow and serve as a positive example for other communities in building a clean and transparent governance system.